2013
DOI: 10.1597/10-170
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Family Members of Children with Cleft Lip and Palate in Hyderabad, India, and Its Rural Outskirts regarding Craniofacial Anomalies: A Pilot Study

Abstract: Objective : This pilot study aimed to understand cultural perspectives on cleft anomalies in the community of Hyderabad, India, and its rural outskirts. Design : Interviews focusing on perceptions of cleft lip and palate were conducted using a 21-item interview guide approved by the director of the Gosla Srinivas Reddy Institute of Craniofacial Surgery (GSR). Settings : Interviews were conducted at GSR, a specialty surgical center located in Hyderabad, India. Patients and Participants : All patients who presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[16] In the present study, more family members were reported to have inferred that cleft is due to “evil spirit” and “wicked people” than mothers (respondents) of the children themselves. Penn et al .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[16] In the present study, more family members were reported to have inferred that cleft is due to “evil spirit” and “wicked people” than mothers (respondents) of the children themselves. Penn et al .…”
Section: Discussionmentioning
confidence: 73%
“…[15] In Hyderabad community, India, a commonly held belief is that cleft lip and palate (CLP) is caused by eclipse. [16]…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These erroneous views of cleft etiology may deter the parents from pursuing treatment for fear of disrupting God's plan. Many factors play a role in why surgery cannot be performed in a timely fashion.…”
mentioning
confidence: 99%
“…Especially when they live in rural areas and away from major cities and medical centers with complete CL/P team. [1][2][3][4] Most of these patients also have lack of medical or insurance coverage for the care of the condition. Therefore, it is common to have the care of these CL/P patients becoming dependent upon charity care and events organized by several groups of Indonesian plastic surgeons.…”
mentioning
confidence: 99%